EVALUATION OF THE PERFORMANCE OF FRENCH BEAN (Phaseolus vulgaris) VARIETIES UNDER ALUMINIUM STRESS ENVIRONMENT - BEAUTY BORANG,; Y. K. SHARMA, (The Bioscan, 2020)
A pot experiment was carried out during 2017-19 to evaluate of the performance of french bean (Phaseolus vulgaris L.) varieties under aluminium stress condition. Three varieties (Selection-9, Anupam-R and Nagaland local) were screened under three levels of aluminium (0, 0.25 and 0.50 cmol kg -1 ) in completely randomized design with three replications. Aluminium application significantly reduced growth and yield parameters, root length and root mass of french bean while number of germination days, test weight, Al content in roots and aluminium uptake in grain was significantly increased. Selection-9 variety produced significantly higher growth, yield parameter and root length as compared to other varieties. But higher test weight was recorded in Nagaland local. Significantly higher Al uptake in grains of french bean was recorded in Selection-9 variety. On the basis of seed yield, the order of superiority of varieties was arranged as Selection-9 > Anupam-R > Nagaland local. The results of the present study lead to a conclusion that the growth and yield of french bean were affected by high aluminium levels. Among the varieties, Selection-9 variety may be recommended for cultivation of french bean in Al stress condition of Nagaland as well as other North Eastern states.